Take the house: Politics of haunting, counter-archive and indigenous resistance in La llorona, by Jayro Bustamante - Cabello del Moral, Pedro (2022)
The feature-film La Llorona (Jayro Bustamante, 2019) aims to rectify a historical debt to Guatemalan indigenous people, a debt that was not paid by the 1996 Peace Accords. The specter of the past is embodied in Alma, a Mayan Kaqchikel servant working in the home of General Monteverde, a man responsible for genocide against indigenous communities. Inverting the concept of haunting, this time it is the torturer and his family who are tormented by past deeds, deeds that had until then remained in a state of moral and juridical impunity. The metaphorical figure of “La Llorona” cries inconsolably from a space beyond death for her children who were assassinated in front of her eyes. Her mourning catalyzes a process of popular justice against Monteverde and his family,as a mounting crowd of protestors surrounds the expresident’s palace and demands justice for the disappeared. The mansion itself turns into a suffocating space that attacks its residents forcing them to reckon with the past. This article interrogates three fundamental aspects of the film. First, it takes up the audiovisual counter-archive in the 2013 trial of Ríos Montt, upon whom the character of Monteverde is based. Second, it discusses how the politics of haunting transcends the film genre of horror and becomes a form of political drama. Finally, it analyzes the decolonial visions proposed by the film as options for a democratic Guatemala.